Structure and catalytic mechanism of glucosamine 6-phosphate deaminase from Escherichia coli at 2.1 Å resolution - Oliva, Glaucius; Fontes, Marcos R.M. [UNESP]; Garratt, Richard C.; Altamirano, Myriam M.; Calcagno, Mario L.; Horjales, Eduardo (Elsevier, 1995)
Background: Glucosamine 6-phosphate deaminase from Escherichia coli is an allosteric hexameric enzyme which catalyzes the reversible conversion of D-glucosamine 6-phosphate into D-fructose 6-phosphate and ammonium ion and is activated by N-acetyl-D-glucosamine 6-phosphate. Mechanistically, it belongs to the group of aldose-ketose isomerases, but its reaction also accomplishes a simultaneous amination/deamination. The determination of the structure of this protein provides fundamental knowledge for understanding its mode of action and the nature of allosteric conformational changes that regulate its function. Results: The crystal structure of glucosamine 6-phosphate deaminase with bound phosphate ions is presented at 2.1 Å resolution together with the refined structures of the enzyme in complexes with its allosteric activator and with a competitive inhibitor. The protein fold can be described as a modified NAD-binding domain. Conclusions: From the similarities between the three presented structures, it is concluded that these represent the enzymatically active R state conformer. A mechanism for the deaminase reaction is proposed. It comprises steps to open the pyranose ring of the substrate and a sequence of general base-catalyzed reactions to bring about isomerization and deamination, with Asp72 playing a key role as a proton exchanger.
Keywords: α/β open structure; Aldose-ketose isomerase; Allosteric enzyme; NAD-binding domain; 2 deoxy 2 aminoglucitol 6 phosphate; 2-deoxy-2-aminoglucitol-6-phosphate; bacterial protein; drug derivative; enzyme inhibitor; epimerase; fructose 6 phosphate; fructose phosphate; fructose-6-phosphate; glucosamine; glucosamine 6 phosphate; glucosamine 6 phosphate isomerase; glucosamine 6-phosphate; glucosamine-6-phosphate isomerase; glucose 6 phosphate; glucose phosphate; isomerase; nicotinamide adenine dinucleotide; phosphate; sorbitol; sugar phosphate; allosterism; binding site; biosynthesis; catalysis; chemical structure; chemistry; drug antagonism; enzymology; Escherichia coli; macromolecule; metabolism; protein conformation; X ray crystallography; Aldose-Ketose Isomerases; Allosteric Regulation; Bacterial Proteins; Binding Sites; Carbohydrate Epimerases; Catalysis; Crystallography, X-Ray; Enzyme Inhibitors; Fructosephosphates; Glucosamine; Glucose-6-Phosphate; Glucosephosphates; Macromolecular Substances; Models, Molecular; NAD; Phosphates; Protein Conformation; Sorbitol; Sugar Phosphates; Bacteria (microorganisms)